Mindfulness, Trust, and Leader Effectiveness: A Conceptual Framework - Stedham, Yvonne; Skaar, Theresa B. (Frontiers in Psychology, 2019)
In this conceptual research, the authors develop an integrative theoretical framework for the relationship between mindfulness and transformational leadership. The model is based on the core aspect of transformational leadership, creating trusting relationships with followers. Core components of the model are self- and social awareness, emotional intelligence, and leadership related competencies such as decision-making, and trust. Direct and indirect relationships between mindfulness and transformational leadership are included in the model. The literature supporting the proposed linkages is presented and discussed and propositions for specific linkages are offered. The paper concludes with the presentation of an exploratory study of the direct relationship between mindfulness and transformational leadership practices. The results support such a relationship.